Transcription factors - CREM: a master-switch in the transcriptional response to cAMP - Lamas, Monica; Foulkes, Nicholas S. (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 1996)
The CREM gene encodes both repressors and activators of cAMP-dependent transcription in a tissue and developmentally regulated manner. In addition, multiple and cooperative phosphorylation events regulate the function of the CREM proteins. CREM plays a key physiological and developmental role within the hypothalamic-pituitary axis. There is a functional switch in CREM expression during the development of male germ cells which is directed by the pituitary hormone FSH . The CREM protein in germ cells is a powerful activator which appears to function as a master-switch in the regulation of postmeiotic genes. CREM is inducible by activation of the cAMP signalling pathway with the kinetics of an early response gene. The induction is transient, cell-specific, does not involve increased transcript stability and does not require protein synthesis. The subsequent decline in CREM expression requires de novo protein synthesis. The induced transcript encodes ICER and is generated from an alternative, intronic promoter. ICER functions as a powerful repressor of cAMP-induced transcription, and represses the activity of its own promoter, thus constituting a negative autoregulatory loop.
Gesehen am 12.10.2017